2022
DOI: 10.14348/molcells.2022.0104
|View full text |Cite
|
Sign up to set email alerts
|

CBP-Mediated Acetylation of Importin α Mediates Calcium-Dependent Nucleocytoplasmic Transport of Selective Proteins in Drosophila Neurons

Abstract: For proper function of proteins, their subcellular localization needs to be monitored and regulated in response to the changes in cellular demands. In this regard, dysregulation in the nucleocytoplasmic transport (NCT) of proteins is closely associated with the pathogenesis of various neurodegenerative diseases. However, it remains unclear whether there exists an intrinsic regulatory pathway(s) that controls NCT of proteins either in a commonly shared manner or in a target-selectively different manner. To diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A study that utilised pharmacological inhibitors of importin activity was able to prevent nuclear importation of pathological Tau proteins and inhibit the cell death that is associated with their expression [ 42 ]. In a similar manner, genetic experiments in Drosophila have shown that Dα3 is required for the transportation of a pathogenic truncated Ataxin-3 variant protein into nuclei, which then results in neuronal toxicity [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study that utilised pharmacological inhibitors of importin activity was able to prevent nuclear importation of pathological Tau proteins and inhibit the cell death that is associated with their expression [ 42 ]. In a similar manner, genetic experiments in Drosophila have shown that Dα3 is required for the transportation of a pathogenic truncated Ataxin-3 variant protein into nuclei, which then results in neuronal toxicity [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously described by Cho et al, 2022 , Park et al, 2020 , Ryu et al, 2022 , adult flies were dissected in Schneider's insect medium (Cat No. S0146; Sigma) to obtain brain samples for immunohistochemical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Calcium has been shown to play a role in regulating the size and shape of the NPC ( Moore-Nichols et al, 2002 ; Erickson et al, 2006 ); however, it is not clear whether or not this action has a significant impact on transport through the pore ( Sarma and Yang, 2011 ). Cho et al, investigating the regulation of the nucleocytoplasmic transport of truncated ataxin-3 (ATXN3) proteins in Drosophila neurons, found that decreasing intracellular calcium levels can reduce the nuclear accumulation of ATXN3; however, this is likely a result of calcium-mediated regulation of CBP rather than the constriction of the pore ( Cho et al, 2022 ).…”
Section: Models Of the Npc And Nucleocytoplasmic Transportmentioning
confidence: 99%